Rancang Bangun Sistem Kontrol Modutrol Valve Menggunakan Sensor Suhu untuk Efisiensi Steam di PT Prakarsa Alam Segar - Zansel Yunison; Nurhabibah Naibaho; Bayu Kusumo (JURNAL ELEKTRO, 2026)
In industrial processes, steam is widely used for heating, drying, and sterilization. However, manual or on–off steam control often leads to energy waste and unstable temperature. This study designs and implements an automatic control system using an RTD PT100 sensor, temperature transmitter, PLC (M221), and modutrol valve. A PID algorithm was applied to proportionally adjust the valve opening according to the actual temperature. The results showed that the system maintained a maximum deviation of ±2 °C from the 160 °C setpoint with a response time of less than 10 seconds. Steam consumption decreased significantly from 4,029 tons (January 2024) to 2,368 tons (May 2025), equivalent to about 41.24% savings. The estimated cost savings range from IDR 332 million to IDR 581 million per month. The system proved effective in improving thermal stability, energy efficiency, and reducing operator workload.